Multitarget Strategy to Address Alzheimer's Disease: Design, Synthesis, Biological Evaluation, and Computational Studies of Coumarin‐Based Derivatives. (28th October 2015) - Montanari, Serena; Bartolini, Manuela; Neviani, Paolo; Belluti, Federica; Gobbi, Silvia; Pruccoli, Letizia; Tarozzi, Andrea; Falchi, Federico; Andrisano, Vincenza; Miszta, Przemysław; Cavalli, Andrea; Filipek, Sławomir; et al.
Abstract: Alzheimer's disease (AD) is a major public health challenge that faces an aging global population. Current drug treatment has demonstrated only symptomatic efficacy, leaving an unmet medical need for a new generation of disease‐modifying therapies. Following the multitarget‐directed ligand approach, a small library of coumarin‐based derivatives was designed and synthesized as a follow‐up to our studies on AP2238, aimed at expanding its biological profile. The coumarin substitution pattern at the 6‐ or 7‐position was modified by introducing alkyl chains of variable lengths and with different terminal amino functional groups. 3‐(4‐{[Benzyl(ethyl)amino]methyl}phenyl)‐6‐({5‐[(7‐methoxy‐6 H ‐indeno[2, 1‐ b ]quinolin‐11‐yl)amino]pentyl}oxy)‐2 H ‐chromen‐2‐one, bearing the bulkiest amine, emerged as a non‐neurotoxic dual acetylcholinesterase (AChE)/butyrylcholinesterase (BuChE) inhibitor, potentially suitable for the treatment of the middle stage of AD. Furthermore, the introduction of a diethylamino spacer, as in 3‐(4‐{[benzyl(ethyl)amino]methyl}phenyl)‐6‐{[5‐(diethylamino)pentyl]oxy}‐2 H ‐chromen‐2‐one and 3‐(4‐{[benzyl(ethyl)amino]methyl}phenyl)‐7‐[4‐(diethylamino)butoxy]‐2 H ‐chromen‐2‐one, led to nanomolar human AChE inhibitors endowed with significant inhibitory activity toward Aβ42 self‐aggregation, whereas the reference compound was completely ineffective. Furthermore, 3‐(4‐{[benzyl(ethyl)amino]methyl}phenyl)‐7‐[4‐(diethylamino)butoxy]‐2 H ‐chromen‐2‐one also showed promising neuroprotective behavior, which makes it a potential candidate for development into a disease‐modifying agent. Abstract : Forget me not : Coumarin derivatives related to AP2238 are reported as disease‐modifying multitarget‐directed ligands for the treatment of Alzheimer's disease. Coumarin‐based derivatives were designed and synthesized with the aim to expand the biological profile of AP2238. One compound emerged as a nanomolar inhibitor of human acetylcholinesterase with significant potency at blocking Aβ42 self‐aggregation, and endowed with additional promising neuroprotective behavior.